KEBIJAKAN PRODUK GLOBAL DALAM MENGHADAPI PASAR INTERNASIONAL - Murni Sofiah; Suhairi Suhairi; Ghilman Rozy Harahap; Nia Andriani; Afif Muhammad Tarigan; Fitrah Dwi Ananda (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The needs of each product by consumers around the world make exporters and importers implement a global product policy which is adjusted by every rule or culture that is different for each country as a condition that must be complied with by business actors/businesses to be able to enter the global market. The purpose of this research is to study a literature review to review global product policies that must be carried out or implemented by business actors in marketing products globally. This research shows that local products are different from global products because marketers must be observant in seeing international market conditions. In order for products and services marketed in global markets to be right on target and receive positive feedback from consumers, marketers must be careful in managing market expansion strategies and positioning global products in international markets